Differences in immunization site pain in toddlers vaccinated with either the 10- or the 13-valent pneumococcal conjugate vaccine - Trück, J; Kelly, S; Jawad, S; Snape, M; Voysey, M; Pollard, A (Lippincott, Williams & Wilkins, 2018)
We investigated immediate immunization pain in 12-month-old children randomized to receive a booster dose of either the 10- (PCV-10) or the 13-valent (PCV-13) pneumococcal conjugate vaccine. Pain was assessed using validated pain assessment tools and crying time. PCV-13 recipients had significantly higher scores on the observer-rated modified behavioral pain scale than did those receiving PCV-10, but the differences were small.Clinical trial registration at Clinicaltrials.gov (NCT01443416).